Feasibility study of particle filters for mobile station receivers - Lunglmayr, Michael; Krüger, Martin; Huemer, Mario (IET Circuits Devices & Systems, 2008)
The application of an equalisation method for mobile station terminals using particle filters is presented. To use particle filters for equalisation, a mathematical model is shown which allows the transmitted symbols to be represented as the state of a stochastic system, which can be estimated by particle filters. The authors propose an equaliser structure with particle filters for application in mobile station receivers, especially for GSM/EDGE (global system for mobile communications/enhanced data rate for GSM evolution). Several improvement strategies, which help to obtain better estimation results with a lower number of particles, are discussed. In addition, performance evaluations of the particle filter equaliser for GSM/EDGE are presented.
elib2cris::1512001600,lunglmayr2008